The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/cddis.2015.221
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26a functions oppositely in osteogenic differentiation of BMSCs and ADSCs depending on distinct activation and roles of Wnt and BMP signaling pathway

Abstract: MicroRNAs (miRNAs) emerge as important regulators of stem cell lineage commitment and bone development. MiRNA-26a (miR-26a) is one of the important miRNAs regulating osteogenic differentiation of both bone marrow-derived mesenchymal stem cells (BMSCs) and adipose tissue-derived mesenchymal stem cells (ADSCs). However, miR-26a functions oppositely in osteogenic differentiation of BMSCs and ADSCs, suggesting distinct post-transcriptional regulation of tissue-specific MSC differentiation. However, the molecular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 55 publications
4
82
0
Order By: Relevance
“…The osteogenic differentiation of BMSCs in vitro results from the activation of some well‐known molecular signaling pathways, such as mitogen‐activated protein kinase (MAPK) signaling pathway, Wnt/beta‐catenin signaling pathway, TGF‐beta/Smad and BMP signaling pathways. In addition, some osteoblast‐specific signal proteins and osteoblast‐specific transcription factors, including Runx2, Osterix and BMP4, also have been proved to play an important role in the osteogenic differentiation of BMSCs . Besides, substantial evidence shows that the inhibited expressions of adipogenic differentiation transcriptional regulators, such as peroxisome proliferator‐activated receptor γ (PPARγ) and CCAAT/enhancer‐binding protein (C/EBP), could promote the osteogenic differentiation of BMSCs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The osteogenic differentiation of BMSCs in vitro results from the activation of some well‐known molecular signaling pathways, such as mitogen‐activated protein kinase (MAPK) signaling pathway, Wnt/beta‐catenin signaling pathway, TGF‐beta/Smad and BMP signaling pathways. In addition, some osteoblast‐specific signal proteins and osteoblast‐specific transcription factors, including Runx2, Osterix and BMP4, also have been proved to play an important role in the osteogenic differentiation of BMSCs . Besides, substantial evidence shows that the inhibited expressions of adipogenic differentiation transcriptional regulators, such as peroxisome proliferator‐activated receptor γ (PPARγ) and CCAAT/enhancer‐binding protein (C/EBP), could promote the osteogenic differentiation of BMSCs .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some osteoblast‐specific signal proteins and osteoblast‐specific transcription factors, including Runx2, Osterix and BMP4, also have been proved to play an important role in the osteogenic differentiation of BMSCs . Besides, substantial evidence shows that the inhibited expressions of adipogenic differentiation transcriptional regulators, such as peroxisome proliferator‐activated receptor γ (PPARγ) and CCAAT/enhancer‐binding protein (C/EBP), could promote the osteogenic differentiation of BMSCs . Many studies have already demonstrated that the disruption of the balance between osteogenesis and adipogenesis in BMSCs leads to disorders of skeletal reconstruction .…”
Section: Introductionmentioning
confidence: 99%
“…MiR-376c inhibits osteoblastogenesis by targeting WNT3 and ARF-GEF-1 -facilitated augmentation of β-catenin transactivation [54]. MiR-26a is majorly target on GSK3β to activate WNT signaling for promoting osteogenic differentiation of BMSCs [55]. In this study, we demonstrated that miR-16-2* can suppress osteoblast differentiation of hBMSCs through regulating WNT5A-mediated WNT pathway.…”
Section: Discussionmentioning
confidence: 70%
“…miR‐26a was widely identified in porcine testicular tissues using RNA‐seq technology (Li, Li, et al., ; Lian et al., ; Luo et al., ; Ran et al., ), suggesting its key roles in swine testicular development and spermatogenesis. Although previous studies reported that miR‐26a plays multiple regulatory roles in cell metabolic processes, including differentiation (Su et al., ), proliferation (Zhou et al., ) and apoptosis (Zhang et al., ). Nevertheless, the regulatory mechanism of miR‐26a is poorly understood in cell autophagy.…”
Section: Discussionmentioning
confidence: 99%